The sociolinguistic situation of ǂHoan, a moribund ’Khoisan’ language of Botswana - Gerlach, Linda; Berthold, Falko (AAeO - Afrikanistik-Aegyptologie-Online, 2011)
In 2010, we conducted a sociolinguistic survey on the moribund ’Khoisan’ language ǂHoan (Ju-ǂHoan), spoken in Botswana at the fringe of the Kalahari Desert. The survey aimed at investigating language use, degrees of multilingualism and language attitude among the ǂHoan speakers. Data collection was done on the basis of a questionnaire. We found that the positive language attitude of individuals towards ǂHoan often conflicts with the community’s attitude towards this language, resulting in a split of actual language use between the family and more formal situations. All ǂHoan speakers are at least bilingual speaking the local lingua franca Kgalagadi (Bantu) besides ǂHoan. Most of them are in fact even trilingual, speaking Gǀui (Khoe-Kwadi) in addition to ǂHoan and Kgalagadi. Most of our results stand in line with an earlier sociolinguistic survey on ǂHoan by Batibo (2005a) which was carried out in 2003. In comparing Batibo’s results to ours, changes in the sociolinguistic situation of ǂHoan as well as differences between the different villages will be pointed out.